Flipbook KVISOFT Teaching Development Language about the Leaf of Historical Tradition in SMA Negeri Karang Pandan - Isa Maryati; Leo Agung; Musa Pelu (BIRCU, 2021)
This study aims to determine whether through the development of flipbook learning media on the material of the legacy of historical traditions can be used to improve student achievement in its function, namely as a learning resource for students in the classroom. This research method includes research and development (R&D). The subjects of this study were 36 students of class X MIPA 1 consisting of 26 female students and 10 male students. The instruments used in this study were interview sheets or questionnaire sheets and observation sheets. The results of this research are in the form of electronic books, flipbooks, legacy of historical traditions. The data taken at the time of the research are validity test data and reliability test data. Based on the results of the research, it shows that the development of flipbook learning media on the material of the legacy of historical traditions as a source of student learning is effective to improve student achievement in history subjects with the results of pre test = 67.2%, post-test 1 = 72.1%, and post. -test 2 = 78.14%. This electronic book, in the form of a flipbook, from the heritage of historical traditions, is used as a teaching and learning resource at SMA N Karangpandan.